A case of axillary lymphadenitis caused by Mycobacterium intracellulare in an immunocompetent patient - Itano, Junko (Respir Med Case Rep, 2019)
Axillary lymphadenitis caused by non-tuberculous mycobacteria is rare and has been reported in immunocompromised hosts. Herein, we report the case of a 67-year-old man without immunodeficiency who developed right axillary lymphadenitis caused by Mycobacterium intracellulare and showed a small nodular shadow in the left pulmonary apex. Biopsy of the right axillary lymph node revealed several epithelioid granulomas, and the culture of the lymph node aspirate yielded Mycobacterium intracellulare. The lymph node lesion and left lung apex shadow resolved spontaneously after careful outpatient monitoring. This case suggests that axillary lymphadenitis could be caused by Mycobacterium intracellulare in an immunocompetent patient.